(untitled) (In situ, 2025)
Rich archaeological heritage of the area of Vranjic is evidenced in ancient spolia incorporated into houses in Vranjic, numerous accidental finds uncovered during construction activities both on land and underwater, references in the writings of Don Frane Bulić, the well-known sunken sarcophagi of Vranjic, and discoveries made during large-scale infrastructure excavations in the early 21st century.